Blood and treasure : Daniel Boone and the fight for America's first frontier - Drury, Bob; Clavin, Thomas (St. Martin's Press, 2021)
It is the mid-eighteenth century, and in the 13 colonies founded by Great Britain, anxious colonists desperate to conquer and settle North America's "First Frontier" beyond the Appalachian Mountains engage in a never-ending series of bloody battles. These violent conflicts are waged against the Native American tribes whose lands they covet, the French, and finally against the mother country itself in an American Revolution destined to reverberate around the world. This is the setting for this epic narrative of none other than America's first and arguably greatest pathfinder, Daniel Boone. This fast-paced and fiery narrative, fueled by contemporary diaries and journals, newspaper reports, and eyewitness accounts, is a stirring chronicle of the conflict over America's "First Frontier."